Descriptive Study on the Application of Early Warning Systems in Emergency Nursing Practice - Desi Alfiani (Indonesian Journal Publisher, 2025)
This study aims to describe and analyze the implementation of the Early Warning System (EWS) in emergency nursing practice as a mechanism to enhance patient safety and clinical responsiveness. Employing a qualitative descriptive approach through a literature-based study, this research integrates data from peer-reviewed journals, academic reports, and relevant clinical documents published between 2015 and 2025. Data were collected through systematic literature review and analyzed inductively using thematic identification, data reduction, conceptual categorization, and interpretation to obtain a comprehensive understanding of EWS application in clinical settings. The findings reveal that EWS contributes significantly to early detection of patient deterioration, reduction of unplanned ICU admissions and cardiac arrests, and improvement in nurses’ clinical judgment and interprofessional collaboration. However, challenges such as limited compliance, alert fatigue, and contextual variations in system effectiveness remain obstacles to optimal implementation. The study highlights the importance of continuous education, system customization, and institutional support to ensure sustainable integration of EWS in emergency care. The results contribute to the theoretical enrichment of patient safety frameworks and offer practical guidance for developing adaptive, evidence-based nursing systems. In conclusion, the application of EWS represents a vital step toward advancing proactive, data-informed nursing practices that strengthen patient safety and professional competence in emergency healthcare environments.